2020
DOI: 10.1002/app.50138
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of epoxy resin filled with nano‐SiO2 treated with a Eugenol epoxy silane

Abstract: Harvesting biobased silane coupling agent to enhance the connection between fillers and epoxy matrix is vital to achieve sustainable and environmentally friendly products. In this work, a eugenol based epoxy silane-coupling agent with high purity was prepared and used for the surface modification of nanosized silica particles. The surface structure composition and physical properties of the modified nano-SiO 2 were characterized through nuclear magnetic resonance, Fourier transferred infrared spectrometer, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…For example, eugenol-derived epoxy modified silica could be used as nano-fillers for commercial epoxy resins, and the mixed system showed good dispersion and improved performance (7.2% enhancement in flexural strength, 17.4% improvement in impact strength, T g increased 12 C). 100 Besides, eugenol-based epoxy resin was also designed as a binary network anti-fouling hydrogels after blended with hydrophilic polymers, which was soaked in the ocean for a month and a half with almost no microbial attachment. 101 In another study, the flame retardancy of eugenol-based epoxy resins modified by siloxane with different chain length was also characterized (LOI as high as 31%).…”
Section: S C H E M Ementioning
confidence: 99%
“…For example, eugenol-derived epoxy modified silica could be used as nano-fillers for commercial epoxy resins, and the mixed system showed good dispersion and improved performance (7.2% enhancement in flexural strength, 17.4% improvement in impact strength, T g increased 12 C). 100 Besides, eugenol-based epoxy resin was also designed as a binary network anti-fouling hydrogels after blended with hydrophilic polymers, which was soaked in the ocean for a month and a half with almost no microbial attachment. 101 In another study, the flame retardancy of eugenol-based epoxy resins modified by siloxane with different chain length was also characterized (LOI as high as 31%).…”
Section: S C H E M Ementioning
confidence: 99%
“…The studies concluded that mechanical, thermal, and structural properties of epoxy adhesives were improved based on the type of the reinforced particles. [4][5][6][7][8] Apart from these common particles, the use of various boron compounds such as boron nitride (BN) has gained importance in recent years. 9 BN, which has a two-dimensional and sp 2 configuration, is highly similar to graphite in terms of its structure, and to graphene in terms of its allotropic form.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins have been used on large scale in our daily lives for coating purpose owing to their adhesives and excellent mechanical performance [1,2]. They have fast curing property and excellent modulus, which assist in fabricating composites having wide variety applications [3].…”
Section: Introductionmentioning
confidence: 99%